How to age disgracefully - Pooley, Clare ([New York] : Pamela Dorman Books, Viking, 2024)
When the city council threatens to sell the doomed community center building, the members of the Social Club join forces with their tiny friends in the daycare next door$1 (Bas well as the teenaged father of one of the toddlers and a geriatric dog$1 (Bto save the building. Together, this group$1 (Bs unorthodox methods may actually work, as long as the police don$1 (Bt catch up with them first.s
Keywords: Older people -- Fiction; Senior centers -- Fiction; Community centers -- Fiction; City councils -- Fiction; Teenage fathers -- Fiction; Dogs -- Fiction; London (England) -- Fiction; Humorous fiction